The myth of literary criticism death - Muhi , Anaam (Al-Adab Journal, 2024)
“Cultural Criticism: A Reading of Arab Cultural Formats by Dr. Abdullah Al-Ghadami” published in 2000, represents a critical work belonging to the post-modernity phase” the research aims to reveal the truth about the death of literary criticism “The statement that came from the post-modernity phase, however, the concept of the death of literary criticism according to Al-Ghadami’sperspective is not the same as that of Ronan McDonald. The reasons differ, in addition to the differences in starting points. On the other hand, the research reveals the intricate connections between literary criticism and adjacent fields. This refutes the myth that literary criticism is in decline, as its foundations and principles remain rooted in these interrelations. Throughout its extensive history, literary criticism has not overlooked these vital connections, The diverse methodologies enriched its domains, sharpened its tools, and reinforced its significance and relevance. Sources from modernity and beyond, along with cultural criticism works, serve as a primary foundation for research.